Non-agglomerated silicon–organic nanoparticles and their nanocomplexes with oligonucleotides: synthesis and properties - Levina, Asya S.; Repkova, Marina N.; Shikina, Nadezhda V.; Ismagilov, Zinfer R.; Yashnik, Svetlana A.; Semenov, Dmitrii V.; Savinovskaya, Yulia I.; Mazurkova, Natalia A.; Pyshnaya, Inna A.; Zarytova, Valentina F. (Beilstein Journal of Nanotechnology, 2018)
The development of efficient and convenient systems for the delivery of nucleic-acid-based drugs into cells is an urgent task. А promising approach is the use of various nanoparticles. Silica nanoparticles can be used as vehicles to deliver nucleic acid fragments into cells. In this work, we developed a method for the synthesis of silicon–organic (Si–NH2) non-agglomerated nanoparticles by the hydrolysis of aminopropyltriethoxysilane (APTES). The resulting product forms a clear solution containing nanoparticles in the form of low molecular weight polymer chains with [─Si(OH)(C3H6NH2)O─] monomer units. Oligonucleotides (ODN) were conjugated to the prepared Si–NH2 nanoparticles using the electrostatic interaction between positively charged amino groups of nanoparticles and negatively charged internucleotide phosphate groups in oligonucleotides. The Si–NH2 nanoparticles and Si–NH2·ODN nanocomplexes were characterized by transmission electron microscopy, atomic force microscopy and IR and electron spectroscopy. The size and zeta potential values of the prepared nanoparticles and nanocomplexes were evaluated. Oligonucleotides in Si–NH2·ODN complexes retain their ability to form complementary duplexes. The Si–NH2Flu nanoparticles and Si–NH2·ODNFlu nanocomplexes were shown by fluorescence microscopy to penetrate into human cells. The Si–NH2Flu nanoparticles predominantly accumulated in the cytoplasm whereas ODNFlu complexes were predominantly detected in the cellular nuclei. The Si–NH2·ODN nanocomplexes demonstrated a high antisense activity against the influenza A virus in a cell culture at a concentration that was lower than their 50% toxic concentration by three orders of magnitude.
Keywords: antiviral effect; non-agglomerated silicon–organic nanoparticles; penetration; Si–NH2·ODN nanocomplexes